Nonchromatographic Separation Techniques - Lewis, Simon (Academic Press, 2013)
Many types of evidence that are encountered in the forensic science laboratory consist of complex mixtures of substances. The complexity of these materials is a double-edged sword to the forensic scientist. The more complex and variable a mixture, the greater is its probative value when comparing known and questioned samples. However, complex mixtures also create analytical problems, as most compounds need to be relatively pure in order to be identified by analytical techniques, such as spectroscopy. While chromatographic and electrophoretic separations are used widely in forensic science, other separation techniques are also important. These can be used both to clean up samples before analysis and for determining useful information about the sample of interest. This article provides an overview of nonchromatographic/electrophoretic separation techniques that are often encountered in forensic analysis.